HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG RESIKO TINGGI KEHAMILAN DENGAN KEPATUHAN KUNJUNGAN ANTENATAL CARE (ANC) - Ropida, Nadia; R, Evi Diliana (Research of Service Administration Health and Sains Healthys, 2022)
Pregnant women is a women who is pregnant, is pregnant mother should pay more attention to their health due to pregnancy and childbird very rizky to the health of mother and baby, one important element of nutrition in pregnancy is iron, iron work for the formation of hemoglobin which transports oxygen and nutrients throughout the body tissue and helps the metabolisme to produce energy, if maternal iron deficiency will cause bleeding, impaired fetal growth in the womb to maternal and fetal death. The specific aims of this study identifies maternal knowledge about high risk pregnancies, maternal adherence in ANC visits, and analyzed the relationship between knowledge of pregnant women in ANC visits compliance. Types of research used in this study is the correlation with the analytic method used is accidental sampling is that every pregnant woman who came checkups that would be given the questionnaire respondents.  In this study, the 35 respondents who met the inclusion criteria in a specified period. After a study found that there is a relationship of knowledge about the pregnant women with high risk pregnancies compliance ANC visits at the health center.  Nearly half of the respondents (42.86% have less knowledge about high-risk pregnancies, and most of the respondents (57.14%)  wayward ANC visit.